Diseminasi Usia Minimal Pelaksanaan Perkawinan Berdasarkan UU No 16 Tahun 2019 Tentang Perubahan UU Nomor 1 Tahun 1974 Tentang Perkawinan di Kec. Besitang - Anggi Nur Nisa Br. Tj (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This Community Service article discusses the dissemination of the minimum age for marriage based on Law no. 16 of 2019 concerning amendments to Law no. 1 of 1974 concerning marriage in Besitang District. This Community Service article aims to advocate for the community, especially teenagers, to know the minimum age limit for marriage. The community service method used is qualitative advocacy. The approach used is a descriptive analysis approach supported by an anthropological and sociological approach. The subjects of this article are teenagers in Besitang District. Data collection for the article uses observation and interviews by the author being directly involved in community service activities. The results of the community service that have been carried out are first, conducting early identification of triggers for teenagers to quickly marry at a young age. Second, dissemination is carried out with humanistic and persuasive communication by conveying the substance of Law no. 19 of 2019. Third, dissemination is carried out to school-age teenagers in the 3 T areas (underdeveloped, outermost, and most remote) with a narrative message of the rights and obligations of teenagers after graduating from school.